The role of self-assessment of learning in university education. Ideas from field research - Roberto Trinchero (Firenze University Press, 2020)
The self-assessment of learning is a process that guides the student in the study and allows him to understand how to perform a task, determine the quality of his performance, compare himself with others on the basis of a shared system of quality criteria. Systematically used, self-assessment can be a vehicle for lasting improvement and reflect on the future performance of the student, in his university, human and professional career, allowing him to develop a working method. This article discusses the possibilities related to self-assessment in university education. The article also describes an empirical research, carried out on students of the three-year degree course in Educational Sciences, aimed at probing the perception that students have of the potential inherent in self-assessment, their ways of using it, and the benefits obtainable in terms of predictive ability of the outcome they will get on the exam.   Il ruolo dell'autovalutazione degli apprendimenti nella formazione universitaria. Spunti dalla ricerca sul campo L'autovalutazione dell'apprendimento è un processo che orienta l'allievo nello studio e gli permette di capire come svolgere un compito, determinare la qualità della propria prestazione, confrontarsi con gli altri sulla base di un sistema condiviso di criteri qualitativi. Utilizzata in modo sistematico l'autovalutazione può essere veicolo di miglioramento durevole e riflettersi sulle prestazioni future dell'allievo, nella sua carriera universitaria, umana e professionale, consentendogli di sviluppare un metodo di lavoro. Il presente articolo discute le possibilità connesse all'autovalutazione nella formazione universitaria. L'articolo descrive anche una ricerca empirica, svolta sugli studenti del corso di laurea triennale in Scienze dell'Educazione, volta a sondare la percezione che gli studenti hanno delle potenzialità insite nell'autovalutazione, i loro modi di utilizzarla, e i benefici ottenibili in termini di capacità previsiva dell'esito che otterranno all'esame.